Increasing Economic Value for Farmers Through Improvements in Beef Cattle Business - Rusdiana, S; Talib, Chalid; Ishak, Andi B Lompengeng; Ferasyi, Teuku Reza (The Faculty of Veterinary Medicine of Syiah Kuala University, 2025)
Background and Aim: The study was conducted in Pabentengang Village, Bajeng District, Gowa Regency, South Sulawesi 2020.Materials and Methods: The study used a survey method of 25 farmers, using questionnaires and interviews. The research location is agricultural land and the community's main business is agriculture and beef cattle. Primary data and secondary data were analyzed descriptively, quantitatively, and economically. The purpose of this paper is to determine the increase in the economic value for farmers through improving beef cattle business.Results: The results showed that the profit of farmers by